Effect of Caffeine and Vitamin D3 on Body Weight of Balb/C Mice - Maimoona Khan and Shahdab Ahmed Butt (Journal of Rawalpindi Medical College, 2016)
Background: To evaluate effect of caffeine and vitamin D3 on body weight of BALB/c mice. Methods: In this experimental study thirty BALB/c mice, three weeks old with average weight 12-14 g were taken and divided into three groups with 10 mice (5 male, 5 female) in each group. The control group G1 was given normal diet prepared at National Institute of Health Islamabad with liberal water intake. Each animal in experimental group G2 was given 10mg of caffeine per100g body weight on alternate day, three days in a week by oral gavage for 60 days. All animals of G3 were given caffeine 10mg/100g body weight on alternate day, three days a week and vitamin D3 0.1μg per day by oral gavage for 60 days. The effect of caffeine and vitamin D3 was assessed by measuring the body weight of the mice at the end of the experiment. Results: Mean final body weight of mice of control group G1 was 31.2 ± 1.932 g while the mean final body weight of experimental groups G2 and G3 was found to be 27.1 ± 2.025 g and 29.2 ± 2.098 g . Mean final body weight of mice of experimental group G2 was less as compared to control group G1 and experimental group G3. Conclusion: The body weight of the mice was reduced due to caffeine consumption while vitamin D3 administration ameliorated the deleterious effect of caffeine on the body weight.